2018
DOI: 10.1037/cdp0000217
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and cortisol in African American emerging adults: The role of neighborhood racial composition.

Abstract: Our results lay the foundation for future research on racial health disparities by suggesting that contextual factors such as neighborhood racial composition can shape the influence race-based discrimination has on health. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Whereas in more diverse neighborhoods or in those with higher percentages of non‐Blacks, discrimination experiences increased (English et al., 2014). An exception to this pattern suggests no relation (Lee et al., 2018). The few studies on this topic with Latinx adults suggest that Latinx individuals who settle in neighborhoods with fewer co‐ethnics will experience more discrimination (Capielo Rosario et al., 2019).…”
Section: Neighborhood and Cultural Stressors And Assetsmentioning
confidence: 99%
“…Whereas in more diverse neighborhoods or in those with higher percentages of non‐Blacks, discrimination experiences increased (English et al., 2014). An exception to this pattern suggests no relation (Lee et al., 2018). The few studies on this topic with Latinx adults suggest that Latinx individuals who settle in neighborhoods with fewer co‐ethnics will experience more discrimination (Capielo Rosario et al., 2019).…”
Section: Neighborhood and Cultural Stressors And Assetsmentioning
confidence: 99%
“…Though some African Americans desire to increase in these means and move into these neighborhoods, non-Black residents may feel threatened by the increasing percentage of Black residents and may exhibit racial discriminatory behaviors (Pager & Shepherd, 2008; Stewart, Baumer, Brunson, & Simons, 2009). Consequently, the psychological and psychophysiological consequences of PRD (e.g., depressive symptoms, cortisol attenuation) are particularly detrimental for African American emerging adults residing in predominantly White neighborhoods (English, Lambert, Evans, & Zonderman, 2014; Lee, Eisman, et al, 2018). Thus, African American emerging adults must contend with challenging social contexts as they begin to interface with social institutions (e.g., educational system, law enforcement) that are potentially more hostile to them, resulting in more PRD and stress.…”
Section: Racial Discrimination and African American Emerging Adulthoodmentioning
confidence: 99%
“…This study responds to calls in the literature to investigate innovative explanations for health disparities by testing interactions of the physical and social environments ( 68 , 69 ). A study that examined the moderating role of the environment on racial discrimination stress and health among African Americans found that discrimination experienced in the previous year was positively associated with cortisol concentration among those residing in neighborhoods with more White residents ( 69 ).…”
Section: Discussionmentioning
confidence: 98%
“…A study that examined the moderating role of the environment on racial discrimination stress and health among African Americans found that discrimination experienced in the previous year was positively associated with cortisol concentration among those residing in neighborhoods with more White residents ( 69 ). Building on the present study's findings by including an additional aspect of the social environment, such as social capital ( 70 ), perceived neighborhood social cohesion ( 71 ), or neighborhood racial makeup ( 69 ), may explain more of the total variance in presence of a chronic health condition among Hispanic/Latino adults.…”
Section: Discussionmentioning
confidence: 99%